METTL3 Promotes Esophageal Squamous Cell Carcinoma Metastasis Through Enhancing GLS2 Expression - Chen, Xiaoting; Huang, Lanlan; Yang, Tingting; Xu, Jiexuan; Zhang, Chengyong; Deng, Zhendong; Yang, Xiaorong; Liu, Naihua; Chen, Size; Lin, Shaoqiang (Frontiers in Oncology, 2021)
Recent studies have identified pleiotropic roles of methyltransferase-like 3 (METTL3) in tumor progression. However, the roles of METTL3 in esophageal squamous cell carcinoma (ESCC) are still unclear. Here, we investigated the function and mechanism of METTL3 in ESCC tumorigenesis. We reported that higher METTL3 expression was found in ESCC tissues and was markedly associated with depth of invasion and poor prognosis. Loss- and gain-of function studies showed that METTL3 promoted the migration and invasion of ESCC cells in vitro. Integrated methylated RNA immunoprecipitation sequencing (MeRIP-Seq) and RNA sequencing (RNA-Seq) analysis first demonstrated that Glutaminase 2 (GLS2) was regulated by METTL3 via m6A modification. Our findings identified METTL3/GLS2 signaling as a potential therapeutic target in antimetastatic strategies against ESCC.